BALINESE ART STUDIOS: THE LEARNING PROCESS OF ART AND CULTURE TO SUPPORT SUSTAINABLE TOURISM - I Gde Agus Jaya Sadguna; I Gusti Agung Mas Krisna Komala Sari; Kumiko Shishido (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Purpose: A lot of perspectives have been discussed about Bali and this paper will discuss it from the angle of the learning process of art and culture in the Balinese art studios in Gianyar Regency. Research methods: The research was conducted on the months of July and August 2019. Qualitative data was obtained during the research because the method of data collection was interviewing the owner of the dance studio. Results and discussions: One of the A’s in tourism is attraction and Bali have a strong attraction for tourists both domestic and foreign tourists. The art and culture is the breath of tourism in the island of Bali, which is based on the Hindu religion. The resources for these art and culture are nurtured in several forms, which one of them is through sanggar or studios, which is a non-formal education institution for learning Balinese art and culture. Various types of art and culture and developed and nurtured in these studios, such as performing arts, fine arts, and local wisdoms. The tourism industry has given positive and negative impacts for Balinese art and culture, depends on how one may argue if seen through different perspectives. Performing arts have flourished in terms of daily performances taken places in hotels and designated performance theaters. The types which can be easily watched are the music and dance of Bali. Conclusion: Tourism in this sense is not a direct aspect but, in the future, has a direct impact: providing culture resources for performances in tourism objects and destinations. This as a part of social sustainability, also the sanggars, is a part of the sustainable tourism family